2010
DOI: 10.1097/yic.0b013e3283334f08
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of antipsychotic drugs in the Italian general population 2000–2005: a focus on elderly with dementia

Abstract: The objective of this study was to evaluate the antipsychotic drug prescribing pattern in the Italian general population, elderly, and especially elderly with dementia, in relation to the safety warnings issued by international regulatory agencies about the risk of cerebrovascular adverse events and mortality in 2004 and 2005. A cohort study was conducted using the electronic medical records of the Italian general practice database 'Health Search/Thales'. On the basis of prescription data, 1-year and monthly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
1
24
0
1
Order By: Relevance
“…A population-based study found that more than 3% of community-dwelling patients are currently treated with antipsychotics in Italy, with a striking increase in the use of atypical antipsychotics over time [2•]. These findings are in accord with data from the United Kingdom [3] and United States, where olanzapine and risperidone were already the most commonly prescribed antipsychotic drugs in 1997 [4].…”
Section: Introductionmentioning
confidence: 57%
“…A population-based study found that more than 3% of community-dwelling patients are currently treated with antipsychotics in Italy, with a striking increase in the use of atypical antipsychotics over time [2•]. These findings are in accord with data from the United Kingdom [3] and United States, where olanzapine and risperidone were already the most commonly prescribed antipsychotic drugs in 1997 [4].…”
Section: Introductionmentioning
confidence: 57%
“…Among patients 70 years and older, approximately onethird of all AP users had an indication for agitation or dementia. In a study from Italy on the basis of an Italian General Practice Database among patients 65 years and older, APs were also rarely used for schizophrenia, but more often for affective psychoses and dementia (Trifiro et al, 2010). In general, the low prevalence of schizophrenia in new AP users aged 65 years and older in our study was expected as incident cases typically occur between adolescence and the mid-30s (Holder and Wayhs, 2014).…”
Section: Indications Of Antipsychotic Usementioning
confidence: 91%
“…In Germany, 25% of older patients with dementia were treated at least once with APs in an observation period of 1 year (Schulze et al, 2013). Studies on older patients from other countries reported an AP prescription prevalence of 3-54% depending on the definition of the study population (Alanen et al, 2006(Alanen et al, , 2008Mann et al, 2009;Nijk et al, 2009;Trifiro et al, 2010;Lustenberger et al, 2011;Wetzels et al, 2011;Kruger et al, 2012;Briesacher et al, 2013;Tjia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We found that 1.06% (2004) to 1.54% (2014) of the HK population were prescribed at least 1 APD and that there was a statistically significant change in prevalence. In comparison, the annual prevalence of APD prescribing in patients from GP settings in Italy was reported as having increased from 1.33% (2000) to 1.74% (2005) . Using a community population sample from the Clinical Practice Research Datalink database in the UK, the prescribing prevalence of APDs and medication used for treating mania was reported as 1.0% and 1.4% in males and females, respectively, in 2010.…”
Section: Discussionmentioning
confidence: 99%